'A colony of shopkeepers': Spaces of consumption in Hong Kong's New Town public housing estates, 1954-1989 - Chan, Vivien (2024)
This thesis focuses on four ‘spaces of consumption’ in the public housing estate in Hong Kong New Towns from 1954 to 1989. These are the hawker pitch, the hawker bazaar, modular and multi-storey markets, and commercial complexes and malls, four spaces that developed alongside the urban development of Hong Kong and the New Territories in the post-war period. My core research question is: How did modern spaces of consumption in Hong Kong’s New Town public housing estates develop as a result of government interaction with everyday shopping practices in the post-war decades? Taking a non-linear approach to history, the thesis articulates the development of Hong Kong through the city’s relationship to consumption practices and processes in the housing estate. It argues that spaces of consumption in public housing estates opened opportunities for Hong Kong residents to negotiate notions of colonial modernity as narrated by the colonial government through public housing and the New Towns. It also presents new readings of design and design history in Hong Kong as not only a lens of urban control, but also as everyday navigations of space. The thesis uses a design history approach employing interdisciplinary methodologies with an emphasis on materiality. In doing so, it engages with contemporary discourse of cultural history, calling for new narratives and perspectives of Hong Kong’s colonial history.